Molecular, Morphological and Chemical Diversity of Two New Species of Antarctic Diatoms, Craspedostauros ineffabilis sp. nov. and Craspedostauros zucchellii sp. nov. - Riccardo Trentin; Emanuela Moschin; André Duarte Lopes; Stefano Schiaparelli; Luísa Custódio; Isabella Moro (Journal of Marine Science and Engineering, 2022)
The current study focuses on the biological diversity of two strains of Antarctic diatoms (strains IMA082A and IMA088A) collected and isolated from the Ross Sea (Antarctica) during the XXXIV Italian Antarctic Expedition. Both species presented the typical morphological characters of the genus Craspedostauros: cribrate areolae, two “fore-and-aft” chloroplasts and a narrow “stauros”. This classification is congruent with the molecular phylogeny based on the concatenated 18S rDNA-rbcL-psbC alignment, which showed that these algae formed a monophyletic lineage including six taxonomically accepted species of Craspedostauros. Since the study of the evolution of this genus and of others raphe-bearing diatoms with a “stauros” is particularly challenging and their phylogeny is still debated, we tested alternative tree topologies to evaluate the relationships among these taxa. The metabolic fingerprinting approach was implemented for the assessment of the chemical diversity of IMA082A and IMA088A. In conclusion, combining (1) traditional morphological features used in diatoms identification, (2) phylogenetic analyses of the small subunit rDNA (18S rDNA), rbcL and psbC genes, and (3) metabolic fingerprint, we described the strains IMA082A and IMA088A as Craspedostauros ineffabilis sp. nov. and Craspedostauros zucchellii sp. nov. as new species, respectively.